2019
DOI: 10.3390/en12091688
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Harvesting Methods to Reduce Weeds on Arable Fields and Collect a New Feedstock

Abstract: During harvesting, grain, straw, and chaff with weed seeds are separated. The chaff is returned to the fields, resulting in weed problems in the subsequent crops. We estimated the fraction of weed seeds a combine harvester could potentially harvest and used various methods to collect the chaff and treat it with heat to kill weed seeds or reduce weed seed germination. Chaff with weed seeds was placed on top of the straw and afterwards baled with the straw as a method to remove weed seeds from the field. We expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…According to findings of Glasner et al (2019) [20], the percentage of weed seeds that can be removed by bailing could change over time. In fact, once the chaff is discharged on the swath, after one day, only 45% of weed seeds remains on top of it, while 35% is found within the swath and the remaining 20% is already lost in the ground.…”
Section: Biomass Lossesmentioning
confidence: 99%
“…According to findings of Glasner et al (2019) [20], the percentage of weed seeds that can be removed by bailing could change over time. In fact, once the chaff is discharged on the swath, after one day, only 45% of weed seeds remains on top of it, while 35% is found within the swath and the remaining 20% is already lost in the ground.…”
Section: Biomass Lossesmentioning
confidence: 99%
“…When seeds were exposed to 250 • C for more than 10 s, most of the species were killed. Our results with exhaust gas were more promising because we did not need durations as long or temperatures as high as Glasner et al [39].…”
Section: Discussionmentioning
confidence: 68%
“…Thereby, the seeds are not incorporated into the soil seed bank, creating new weed problems in the coming season. However, many weed species shatter a smaller or larger proportion of their seeds before harvest [38,39]; therefore, the effect strongly depends on the weed composition in the field. Walsh and Powels [40] found that some of the most important weed species in Australia-L. rigidum, Raphanus raphanistrum L., Bromus spp., and Avena fatua L.-retained 85%, 99%, 77%, and 84% of their seeds above a 15 cm harvest cutting height at wheat (Triticum aestivum L.) maturity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have now shown that a large proportion of seeds produced during the growing season of common weed species potentially can be collected and removed or destroyed [43][44][45] by a combine harvester at crop harvest. The next step will be to test how large a fraction of this potential a combine harvest actually collects, as it depends on several factors such as harvest height and the number of seeds dropping to the soil surface under the harvesting process.…”
Section: Discussionmentioning
confidence: 99%